PENGARUH PENGGUNAAN MEDIA INTERAKTIF TERHADAP HASIL BELAJAR IPA - Septi Ristiyanti; Hidayati Hidayati; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The purpose of this descriptive study to determine the tendency of learning result of Science Study Program whose learning using interactive media and without interactive media. Comparative, aims to determine differences of learning result between learning using interactive media and without interactive media. The kind of this research is descriptive-comparative wich is â€œQuasi Eksperimentâ€. The population in this research is the whole of students in class VIII of SMP Negeri 1 Banguntapan in academic year 2015/2016. The technique of data collection uses the documentation and test technique. Data analysis is deccriptively used with ideal norma curve criteria and comparatively with test. Descriptively, the result of the research shows that the trend of learning result that learning using interactive media include the very high criteria, without interactive media include the high criteria. Comparatively, there are effectÂ  of the use interactive media to learning result of science in class VIII SMP Negeri 1 Banguntapan in academic year 2015/2016.